On the way to forming the integrated educational space - Igor V. Titovich (Moscow Polytechnic University, 2022)
The author presents the review of the "Dictionary of the agreed terms and definitions in the education sphere for the CIS member states". The edition has been prepared by the group of authors from the Institute of higher education quality of the National University of Science and Technology MISIS.